Spectrum of Functional Abdominal Pain Disorders in Children and Their Clinical, Social Characteristics: A Cross‐Sectional Study - Jayendra Seetharaman; Ujjal Poddar; Anshu Srivastava; Moinak Sen Sarma; Surender Kumar Yachha (JGH Open)
ABSTRACT Background/Aims Pediatric functional abdominal pain disorders (FAPDs) subtypes; functional dyspepsia (FD), irritable bowel syndrome (IBS), functional abdominal pain‐not otherwise specified (FAP‐NOS), and abdominal migraine (AM) are influenced by demographic and social factors. The study aimed to evaluate the spectrum and demographic and social factors associated with FAPD subtypes. Methods Consecutive children (< 18 years) diagnosed with FAPD subtypes according to ROME‐IV criteria between April 2018 and March 2020 were included. The clinical, demographic, and social parameters were analyzed between various subtypes of FAPD, and factors responsible for severe symptoms were studied. Results A total of 479 children (mean age 12.34 ± 3.82 years, 60% boys) were included. FAP‐NOS (63%) was the most commonly diagnosed subtype followed by IBS (17.4%) and FD (15%). The age at presentation, site of pain, duration of symptoms, and associated symptoms were significantly different among the three main subtypes (p < 0.001). Stressors could be identified in 39.3% and academic pressure (22.3%) was the most common. Family members with functional disorders (OR: 2.21, 95% CI: 1.31–3.42, p = 0.02), presence of stressors (OR: 2.03, 95% CI: 1.14–3.65, p = 0.016), and rural origin (OR: 1.75, 95% CI: 1.08–2.83, p = 0.023) predicted severe symptoms. Conclusions FAP‐NOS is the most common FAPD subtype in children in India. Children with FAP‐NOS are much younger than other subtypes of FAPD. The presence of stressors and functional disorders in family members could be associated with severe symptoms. However, it mandates more prospective studies to validate the findings.